Determination of flexural capacity for GFRP-reinforced concrete beams retrofitted using external CFRP sheet. (October 2020) - Elbana, Abdalla; Junaid, M. Talha
Abstract: This paper investigates the flexural capacities and deflection characteristics of ordinary portland cement-based concrete (OPCC) and geopolymer concrete (GPC) beams reinforced with glass-fiber-reinforced polymer bars (GFRP). The applicability of carbon-fiber-reinforced polymer (CFRP) sheets as a strengthening technique for such systems is also studied. A total of 15 beams were tested under a four-point quasi-static load. Eight beams served as a reference, while the remaining seven were damaged by loading up to 50% of their load capacities and subsequently strengthened with CFRP sheets. Moment capacities, strain development, load-deflection relationships, and failure modes are reported. The ACI 440.1R-06 guideline was found to be appropriate to give conservative estimates of flexural capacities of control beams for both OPCC and GPC. The previously proposed deflection models for OPC beams reinforced with FRP bars may be used to determine the deflection of GPC composite beams provided that the modulus of elasticity is adequately adjusted for such concretes. For the strengthened beams, however, the ACI 440.2R17 process does not account for the dissimilarity between the CFRP and GFRP modulus values and therefore overestimates the capacity of these unique composites. Finally, a factor (λ) is proposed to consider the contribution to the flexural capacity of GFRP bars in such strengthened system.